1989
DOI: 10.2307/2409166
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial-DNA Variation in the Crested Newt Superspecies: Limited Cytoplasmic Gene flow Among Species

Abstract: The crested newt has a widespread European distribution and encompasses four taxa recently elevated to full species: Triturus cristatus, T. carnifex, T. dobrogicus, and T. karelini. These are distinct on morphological, chromosomal, and isozymic grounds and have fairly sharp transition zones. A widespread survey (12 countries, 49 geographic sites, 210 individuals) of mtDNA variation (20-27 restriction enzyme sites mapped per individual) was made in order to 1) correlate mtDNA variation with morphological featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
118
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(129 citation statements)
references
References 0 publications
10
118
0
1
Order By: Relevance
“…Although intermediate values of both traits have been demonstrated in hybrids between various pairs of closely related newt species (Wallis and Arntzen, 1989;Arntzen and Wallis, 1994;Brede et al, 2000), present results also confirmed morphological intermediacy for T. carnifex  T. dobrogicus offspring. This suggests that F1 hybrids poorly fit morphological space of both parental species.…”
Section: Article In Presssupporting
confidence: 82%
See 1 more Smart Citation
“…Although intermediate values of both traits have been demonstrated in hybrids between various pairs of closely related newt species (Wallis and Arntzen, 1989;Arntzen and Wallis, 1994;Brede et al, 2000), present results also confirmed morphological intermediacy for T. carnifex  T. dobrogicus offspring. This suggests that F1 hybrids poorly fit morphological space of both parental species.…”
Section: Article In Presssupporting
confidence: 82%
“…Both species belong to the Triturus cristatus species group, in which members meet at narrow contact zones between their parapatric geographical ranges and their interspecific crosses produce viable and morphologically intermediate offspring (Callan and Spurway, 1951;Wallis and Arntzen, 1989;Macgregor et al, 1990;Brede et al, 2000). The most pronounced morphological differences between these species are visible in forelimb length (FLL) (T. carnifex 4T.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proven that loss of genetic diversity would occur in such repetitive contractions and expansions, which would be greater in the species with rapid dispersal than in those with slow dispersal (Hewitt, 1996). Correspondingly, the genetic diversity in the northern population is usually lower than that of the populations remaining in the south (Cooper et al, 1995;Gill et al, 1993;Wallis and Arntzen, 1989).…”
Section: Effect Of Glaciations On P Eudamippusmentioning
confidence: 99%
“…Triturus ivanbureschi Arntzen andWielstra 2013 (in Wielstra et al, 2013b) comprises two candidate species and we refer to the collective as T. ivanbureschi sensu lato . The two candidate species comprising T. ivanbureschi sensu lato were initially identified based on their deep genetic divergence of mtDNA, on par with recognized crested newt species (Wallis & Arntzen, 1989;Wielstra et al, 2010). There are no known morphological differences to distinguish the two (Arntzen, 2003;Ivanović et al, 2013).…”
Section: Introductionmentioning
confidence: 99%